Instrumen Deteksi Kesiapan Belajar Anak Usia Dini Pada Aspek Kognitif - Sima Mulyadi; Edi Hendri Mulyana; Mia Rahmawati (JURNAL PAUD AGAPEDIA, 2023)
This study aims to detect early childhood learning readiness in cognitive aspects. The type of research used is Educational Design Research (EDR). This study uses the Reeves model, with two trials. The subjects in this study were fourteen parents of children aged 6-7 years and fourteen PAUD teachers. The instrument used is a questionnaire (check list) and documentation. The research procedure consists of 4 stages, namely 1) Analysis and exploration; 2) design and construction; 3) evaluation and reflection; 4) Maturing intervention and theoretical understanding. The result of the research is that the instrument for detecting early childhood learning readiness in cognitive aspects can be used by teachers and parents to detect children's learning readiness.Penelitian ini bertujuan untuk mendeteksi kesiapan belajar anak usia dini pada aspek kognitif. Jenis penelitian yang digunakan yaitu Educational Design Research (EDR). Penelitian ini menggunakan model Reeves, dengan dua kali uji coba. Subjek dalam penelitian ini adalah empat belas orang tua anak usia 6-7 tahun dan empat belas guru PAUD. Instrumen yang digunakan yaitu lembar angket (check list) dan dokumentasi. Prosedur penelitiannya terdiri dari 4 tahapan yaitu 1) Analisis dan eksplorasi; 2) desain dan konstruksi; 3) evaluasi dan refleksi; 4) Maturing intervention dan theoretical understanding. Hasil penelitian adalah instrumen deteksi kesiapan belajar anak usia dini pada aspek kognitif dapat digunakan oleh guru dan orang tua untuk mendeteksi kesiapan belajar anak.